Welcome Inside the Casino Cottage: Challenging the Notions of “Risk” in Online Casino Advertising through a Context-Attentive Discourse Analysis of a Swedish Brand’s Ad Videos from 2014-2022 - Kroon, Åsa (Critical Gambling Studies, 2023)
Gambling advertising’s use of celebrities, humor, and representations of happy people who Win Big, in narratives told in brash colored, high-pitched ads, are argued to increase the risk for gambling problems, or worse, addiction. Online casino ads have been subject to particular legislative attention partly for these reasons, as well as for being increasingly targeted to women who, by some, are judged to be especially vulnerable to such marketing. This paper presents a context-attentive, multimodal discourse analysis of a Swedish online casino brand’s advertising videos from 2014-2022. The study illustrates how general statements regarding risk in relation to (online casino) gambling ads’ content dramatically reduces their potential cultural significance to audiences. It is argued that one should, to a greater extent, treat these adverts as complex and socio-culturally rooted texts whose content may not so easily be written off as simply “risky,” to women or otherwise.